2012
DOI: 10.3389/fpsyg.2012.00193
|View full text |Cite
|
Sign up to set email alerts
|

The Attentional Drift-Diffusion Model Extends to Simple Purchasing Decisions

Abstract: How do we make simple purchasing decisions (e.g., whether or not to buy a product at a given price)? Previous work has shown that the attentional drift-diffusion model (aDDM) can provide accurate quantitative descriptions of the psychometric data for binary and trinary value-based choices, and of how the choice process is guided by visual attention. Here we extend the aDDM to the case of purchasing decisions, and test it using an eye-tracking experiment. We find that the model also provides a reasonably accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
300
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(331 citation statements)
references
References 58 publications
21
300
0
1
Order By: Relevance
“…It extends multiattribute models of consumer decision-making in economics (8-10), psychology (11)(12)(13), and marketing (14,15) to both charitable giving and motivation crowding-out contexts. In addition, the proposed role of donor mindsets extends previous literature in psychology (16,17) by suggesting that these mindset effects may be mediated by saliency and attention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It extends multiattribute models of consumer decision-making in economics (8-10), psychology (11)(12)(13), and marketing (14,15) to both charitable giving and motivation crowding-out contexts. In addition, the proposed role of donor mindsets extends previous literature in psychology (16,17) by suggesting that these mindset effects may be mediated by saliency and attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One commonly cited theory (6,7) suggests that gifts reduce the donation's ability to act as a self-signal of altruism, thus reducing motivation to donate. Alternatively, attention-based multiattribute choice models (8)(9)(10)(11)(12)(13)(14)(15) predict that individuals overweight salient attributes and underweight shrouded attributes when making choices. If the thankyou gift is a particularly salient attribute, this may cause the donor to underweight less salient intrinsic motives such as altruism, potentially leading to lower motivation to donate.…”
mentioning
confidence: 99%
“…2), consumer purchasing decisions, and temporal discounting decisions (Krajbich, Armel and Rangel 2010;Krajbich and Rangel 2011;Krajbich et al 2012). In several of these studies visual attention was also incorporated into the DDM and it was shown that there is a reliable correspondence between gaze time and choices.…”
Section: Drift-diffusion Model Of Choicementioning
confidence: 99%
“…This model [the attentional DDM (aDDM)] has been shown to accurately model choices and mean reaction times in two-and three-alternative economic decisions (6,8,9). This model clearly shows how fixation durations and fixation sequences affect choices.…”
mentioning
confidence: 99%